Developing an Evaluation Framework for Immersive Learning Experiences for Software Engineering Project Course - Nurfauza, Binti Jali; Norazian, Mohd Hamdan; Cheah, Wai Shiang; Suriati Khartini, Jali (2021)
Most of the principles and concepts that need to be taught in Software Engineering courses are hard to share the realistic experiences because it is difficult to give the student practical exposure to the insight and processes involved. There is a non-existent approach to conveying the concepts of applying Agile Scrum and Team Software Process (TSPi) that involve learner, instructor and business stakeholder. This paper will explain the concept of a framework for efficiently building an immersive learning environment for both learner and instructor of Software Engineering Project course with the involvement of business stakeholder. This provides an opportunity for learning to be more focused on learning design through the prism of immersive environments rather than the collection of information. The online surveys were disseminated to third-year students who took the Software Engineering Laboratory course and the projects' stakeholders. This study aims to gain feedback from both sides on the effectiveness and suitability of the framework and concept in teaching and learning the course. Our experience in the creation, conduct and iteration of the course is outlined in this paper. It ends by assessing the degree to which we were able to achieve the course objectives established by the students and stakeholders.